MANAGEMENT OF CONVENTIONAL ACTIVE ARCHIVES OF BANK DKI MAYOR OF CENTRAL JAKARTA IN THE DIGITAL AGE - Nisa Humairoh; Christian Wiradendi Wolor; Maulana Amirul Adha (Yayasan Education and Social Center, 2023)
This research aims so that in the future conventional archives are directed to digitization by utilizing technology and improving the quality of management of conventional active archives in the digital era. The method used is qualitative by using the case study method. Data collection techniques in this study were carried out through observation, interviews and others. While the data analysis used is data reduction, data presentation, data collection and conclusions or verification. The results of the study show that archive management in the implementation of conventional active archive management processes at Bank DKI mayor of central Jakarta in the digital era is carried out through the creation, storage, use, maintenance, depreciation and destruction of archives. However, there are obstacles encountered such as limited facilities and infrastructure, lack of understanding in information technology in the digital era, the number and quality of human resources are inadequate and still limited, difficulties in converting archive centers into data centers, difficulties in recovering conventional active archives. In overcoming this problem there are. Efforts made in dealing with obstacles include procuring and adding archive facilities and infrastructure, providing understanding of employees, adding employees who have expertise in the field of archiving, transitioning archive centers to data centers and rediscovering conventional active archives but until currently, the management of conventional active archives at Bank DKI, Mayor of Central Jakarta, has not been fully digitized properly and correctly